FRI0068 Sustaining remission as defined by the new acr/eular criteria leads to better quality of life in patients with rheumatoid arthritis. (23rd January 2014) - Shidara, K.; Nakajima, A.; Inoue, E.; Hoshi, D.; Tanaka, E.; Inoue, Y.; Kobayashi, A.; Seto, Y.; Momohara, S.; Taniguchi, A.; Yamanaka, H.
Abstract : Background: Remission is a therapeutic target in the management of rheumatoid arthritis (RA). New remission criteria proposed by the ACR/EULAR in 2010 must be validated to determine whether they are useful for achieving better long-term outcome. At the 2010 ACR annual meeting, we demonstrated that sustaining remission contributed to maintaining physical function irrespective of which criteria were used and that Boolean-based criteria were better than other criteria. However, the utility of these criteria for maintaining daily quality of life (QOL) in RA patients has not been well elucidated. Objectives: To evaluate the improvement of QOL in a large cohort of RA patients (IORRA) who met various remission criteria. Methods: The IORRA cohort study is a single-institute, large observational, cohort study of RA conducted in the Institute of Rheumatology, Tokyo Women's Medical University, Japan. A database of physicians' assessments, patients' assessments, and laboratory data has been created and the data have been collected biannually (every April and October) since October 2000. Data collected between April 2008 and October 2010 (six data collections) from 972 RA patients who fulfilled DAS28 remission criteria at least once, were analyzed. These patients were evaluated many times according to different remission criteria (Boolean trial and practice, index of CDAI, SDAI or DAS28). QOL was assessed by the European QOL-5 dimensions (EQ-5D) score. The proportion of patients with EQ-5D score aggravation during the observation period was calculated according to the number of times that patients fulfilled remission criteria. Multivariate analysis of non-aggravation of the QOL score was carried out after adjusting for sex, age, disease duration, body mass index, rheumatoid factor, and physical function measured by the Japanese version of the Health Assessment Questionnaire (J-HAQ). Results: Among 972 patients (women, 76.9%; mean age, 57.0 years; disease duration, 11.2 years; baseline DAS28, 2.0; and EQ-5D, 0.875) EQ-5D score was aggravated in 7.6%, 8.6%, 9.1%, 10.2%, and 11.6% of patients who met the Boolean trial, Boolean practice, SDAI index, CDAI index, and DAS28 criteria for all six IORRA data collection periods, respectively. QOL was aggravated in 35.2–38.1% of patients who met DAS28 remission criteria at least once but not other criteria during the 2.5 years of observation. The odds ratio (OR) of aggravated EQ-5D score was 1.66 (95%CI 1.11-2.51, p<0.05) in women, 1.18 (95%CI 1.03-1.35, p<0.05) in patients with increase in age of 10 years, and 0.90 (95%CI, 0.62-1.34), 0.45 (95%CI, 0.28-0.71), and 0.21 (95%CI, 0.12-0.35) in patients who met Boolean trial remission criteria 1 or 2, 3 or 4, and 5 or 6 times, respectively, compared to patients who never met these criteria. Conclusions: Sustaining remission defined by the new ACR/EULAR criteria (compared to CDAI, SDAI index of remission criteria, or DAS28 remission criteria) results in better QOL in RA patients. To improve long-term QOL in RA patients, fulfillment of the new remission criteria is needed. Disclosure of Interest: K. Shidara: None Declared, A. Nakajima: None Declared, E. Inoue: None Declared, D. Hoshi: None Declared, E. Tanaka: None Declared, Y. Inoue: None Declared, A. Kobayashi: None Declared, Y. Seto: None Declared, S. Momohara Speakers bureau: Abbott Japan, Chugai Pharmaceutical, Eisai, Mitsubishi Tanabe Pharma, Takeda Pharmaceutical, A. Taniguchi: None Declared, H. Yamanaka Grant/research support from: IORRA study is supported by Asahikasei Kuraray Medical Co., Ltd., Abbott Japan Co., Ltd., Asahikasei Pharma Corporation, Astellas Pharma Inc., AstraZeneca K.K., Bristol-Myers Squibb, Chugai Pharmaceutical Co., Ltd., Daiichi Fine Chemical Co., Ltd., Daiichi Sankyo Co., Ltd., Dainippon Sumitomo Pharma Co., Ltd., Eisai Co., Ltd., GlaxoSmithKline K.K., Hisamitsu Pharmaceutical Co., Inc., Janssen Pharmaceutical K.K., Japan Tobacco Inc., Kaken Pharmaceutical Co., Ltd., Kissei Pharmaceutical Co., Ltd., Kowa Pharmaceutical Co. Ltd., Maruho Co., Ltd., Mitsubishi Chemical Medience Corporation, Mitsubishi Tanabe Pharma Corporation, Mochida Pharmaceutical Co. Ltd., MSD K.K., Mundipharma K.K., Nippon Chemiphar Co., Ltd., Nippon Shinyaku Co., Ltd., Novartis Pharma K.K., Otsuka Pharmaceutical Co., Ltd., Pfizer Japan Inc., Sanofi-Aventis K.K., Santen Pharmaceutical Co., Ltd., Sanwa Kagaku Kenkyusho Co., Ltd., Sekisui Medical Co., Ltd., Shionogi Co., Ltd., Taishotoyama Pharmaceutical Co., Ltd., Takeda Pharmaceutical Co. LTD., Teijin Pharma Limited, Torii Pharmaceutical Co., Ltd., UCB Japan Co. Ltd., ZERIA Pharmaceutical Co., Ltd., Speakers bureau: Abbott, AstraZeneca, Bristol-Myers Squibb, Chugai, Eisai, Janssen, Mitsubishi Tanabe., Pfizer, Takeda, Teijin Pharma, UCB